Cheap street : London's street markets and the cultures of informality, c.1850--1939. - Kelley, Victoria (Manchester University Press, 2019)
From around 1850, London's street markets grew in number and scale, giving working-class Londoners a site for shopping, entertainment and sociability. Cheap Street is the first major study of this subject, analysing the street markets as a component of London's lively informal economy, and providing new insights into urban and consumer geographies.